m6A RNA modifications are measured at single-base resolution across the mammalian transcriptome - Hu, Lulu; Liu, Shun; Peng, Yong; Ge, Ruiqi; Su, Rui; Senevirathne, Chamara; Harada, Bryan T.; Dai, Qing; Wei, Jiangbo; Zhang, Lisheng; Hao, Ziyang; Luo, Liangzhi; et al. (Nature biotechnology, 2022)
Functional studies of the RNA N 6 -methyladenosine (m 6 A) modification have been limited by an inability to map individual m 6 A-modified sites in whole transcriptomes. To enable such studies, here, we introduce m 6 A-selective allyl chemical labeling and sequencing (m 6 A-SAC-seq), a method for quantitative, whole-transcriptome mapping of m 6 A at single-nucleotide resolution. The method requires only ~30 ng of poly(A) or rRNA-depleted RNA. We mapped m 6 A modification stoichiometries in RNA from cell lines and during in vitro monocytopoiesis from human hematopoietic stem and progenitor cells (HSPCs). We identified numerous cell-state-specific m 6 A sites whose methylation status was highly dynamic during cell differentiation. We observed changes of m 6 A stoichiometry as well as expression levels of transcripts encoding or regulated by key transcriptional factors (TFs) critical for HSPC differentiation. m 6 A-SAC-seq is a quantitative method to dissect the dynamics and functional roles of m 6 A sites in diverse biological processes using limited input RNA. m 6 A-SAC-seq uses chemical labeling to quantify m 6 A at single-base resolution in the mammalian transcriptome.